Combustion and performance characteristics of an HCCI engine utilizing trapped residual gas via reduced valve lift. (5th May 2016) - Çınar, Can; Uyumaz, Ahmet; Polat, Seyfi; Yılmaz, Emre; Can, Özer; Solmaz, Hamit
Highlights: Indicated thermal efficiency was found to be higher at 17.91% with In 5.5-Ex 3.5. HCCI combustion was achieved by avoiding knocking at high loads via residual gas trap. Auto ignition chemical reactions were retarded with residual gases. Trapping exhaust gases is a feasible strategy to control HCCI combustion phasing. Abstract: In this study, the effects of residual gas fraction (RGF) on homogeneous charged compression ignition (HCCI) combustion were investigated experimentally. Experiments were performed at different lambda values and constant intake air temperature of 80 °C with the blend of 20% n-heptane and 80% isooctane (PRF80) test fuel. In order to obtain exhaust gas trapping and HCCI operation, two different cam mechanisms, having reduced valve lift, were used. Valve lift values of 5.5 mm (In5.5) and 3.5 mm (In3.5) were used in cam mechanisms. Exhaust valve lift values were 3.5 mm (Ex3.5) for both cam mechanisms. The experimental findings showed that in-cylinder pressure and heat release rate decreased using In5.5-Ex3.5 cam mechanism compared to In3.5-Ex3.5. More residual gases were trapped using In3.5-Ex3.5 cam mechanism. Combustion was also retarded with low lift cams due to more trapped residual gases. Indicated thermal efficiency was found 28.4% with In 3.5-Ex 3.5 whereas obtained 33.57% with In 5.5-Ex 3.5 cam mechanism at 1000 rpm. RGF was computed as 20.12% and 21.12% with In 5.5-Ex 3.5 and In 3.5-Ex 3.5 cam mechanisms, respectively, at 1000 rpm engine speed and stoichiometric air/fuel ratio. Moreover, indicated thermal efficiency was found to be higher about 17.91% with In 5.5-Ex 3.5 according to In 3.5-Ex 3.5 at 1200 rpm. Consequently, it was observed that HCCI combustion phasing can be controlled using low lift cams. It was seen that trapping exhaust gases in the cylinder is a feasible and practical method to control combustion phasing and spread out the HCCI operating range. In addition, stable HCCI combustion can be achieved trapping exhaust gases resulting in avoiding knocking especially at high engine loads.